The impact of job satisfaction, organizational commitment, and empowerment on employee loyalty in Malaysian Resources Corporation Berhad / Nurul Afni Shazrini Ahmad Suwadi - Ahmad Suwadi, Nurul Afni Shazrini (Faculty of Business and Management, 2014)
Employees are the most vital asset for organizational development. It is the source that makes other sources use and gets best return out of them. In order to get the best of employees, the organization and management need to require massive moves. Thus, managing employees has become an art. Management always tries to use that art to satisfy their employees. If the employees feel satisfied in their job, it will be benefit to the organization. Therefore, the objective of this study is to measure the positive impact of job satisfaction, organizational commitment, and empowerment on employee loyalty in Malaysian Resources Corporation Berhad (MRCB). This study was also conducted in order to find the relationship between these variables. The three independent variables which are job satisfaction, organizational commitment, and empowerment will be used to analyze and examined this study thoroughly and in details.